Regional Economic Development Strategy in Preparation for the Establishment of a New Autonomous Region in Indonesia - Firmansyah, Lepi Ali; Soetarto, Endriatmo; Kusnadi, Nunung (Universitas Muhammdaiyah Surakarta, 2014)
In general, the purpose of this study is to analyze the economic potential readiness in South Cianjur Development Region and formulate economic development strategies in an effort to achieve independence in the execution of development. The method of analysis used in this study are the analysis of Location Quotient, analysis of Limpitan Sejajar system, analysis of Internal Factor Evaluation Matrix (IFE Matrix) and External Factor Evaluation Matrix analysis (EFE matrix), analysis of matrix Strength-Weakness-Opportunities-Threats (SWOT), and analysis of Quantitative Strategic Planning Matrix (QSPM). The analysis showed that South Cianjur has potential, especially on: (1) agriculture, livestock, fisheries and forestry sector; (2) the mining and quarrying sector; and (3) the tourism sector. Based on IFE- EFE matrix analysis and SWOT analysis, South Cianjur district has priority strategy that uses internal strength to take advantage of external opportunities (S-O strategies). Selected strategic priorities are: (1) the development of agriculture by ecotourism, ecotourism and community forestry pattern; (2) the development of agroindustry; and (3) select and promote the spesific commodity to provide value-added (GDP and PAD).